Properties of Noninfectious and Transforming Viruses Released by Murine Sarcoma Virus-Induced Hamster Tumor Cells - Gazdar, A. F. (1973)
The cell culture lines HTG2 and HTG3 were established from a transplantable hamster tumor induced by a murine sarcoma virus (strain Gz-MSV) after 17 and 60 in vivo passages, respectively. The viruses released by these two cell lines markedly differ in morphology, antigenic composition, infectivity, transforming ability, and enzymatic activity. HTG2 virions contained the sarcoma genome but were noninfectious for mouse and hamster cells (S+H-virus). HTG3 virions transformed hamster but not mouse cells. Whereas HTG2 cells and its virus contained murine type C virus gs-1 antigen, all HTG3 clonal lines expressed both murine and hamster type C virus gs-1 antigens. The RNA-dependent DNA polymerase activity of HTG2 virus was very low, whereas that of HTG3 virus was relatively high. HTG2 virions contained electron-lucent centers only. HTG3 virus consisted of the expected mixture of virions with electron-dense and electron-lucent centers. Many broken or incomplete virions were present in both viruses. HTG2 virus is a noninfectious “defective” sarcoma virus without detectable helper virus. Data obtained in these experiments suggest that HTG3 virus is a hamster type C virus pseudotype of Gz-MSV (Gz-MSV [HaLV]). The genome of Gz-MSV is capable of antigenic expression in heterologous cells and in the presence of heterologous viruses. Attempts to chemically activate hamster type C virus (HaLV) from HTG2 cells were unsuccessful. The HTG1 cell culture line, established from another Gz-MSV-induced hamster tumor, initially released a virus indistinguishable from the HTG2 virus. After in vitro passage, spontaneous activation of HaLV occurred in HTG1 cells, and the resultant Gz-MSV (HaLV) had properties similar to those of the HTG3 virus.